Information technology for management : emerging research and applications ; 15th Conference, AITM 2018, and 13th Conference, ISM 2018, held as part of FedCSIS Poznan, Poland, September 9-12, 2018, revised and extended selected papers /: emerging research and applications ; 15th Conference, AITM 2018, and 13th Conference, ISM 2018, held as part of FedCSIS Poznan, Poland, September 9-12, 2018, revised and extended selected papers. (2019) - Unknown
No abstract available